Melioidosis in Kelantan : disease outcome, distribution and genotyping of burkholderia pseudomallei from patients and environments - Adib, Siti Munirah Mohd (2022)
Melioidosis is an infectious disease caused by highly pathogenic soil-dwelling bacteria known as Burkholderia pseudomallei. This infectious disease has a wide range of non-pathognomonic clinical spectrum with high mortality rates worldwide. Melioidosis is underdiagnosed and underreported which has become a global burden due to the lack of awareness and knowledge among the population. Melioidosis is endemic in Malaysia, however, there is paucity of data on the distribution pattern of the disease and the causative agent. Therefore, this study is conducted to identify the disease outcome, distribution and genotyping of B. pseudomallei isolates in Kelantan, the north-eastern state of Malaysia. The demographic and clinical data of patients were analysed by SPSS software while the genetic interrelationship between clinical and environmental variants was analysed by MLST method. Study of a total of 70 positive cases showed high prevalence of melioidosis among males (32.9%, n=23), middleaged group (75.7%, n=53) and Malay ethnic group (98.6%, n=69). Diabetes mellitus was the major comorbidity among the patients (65.7%, n=46). Mortality rate of 37.1% (n=26) was reported, of which septicemic melioidosis carried high mortality rate. Systemic melioidosis, formation of abscess and sepsis/septic shock were significantly associated with the outcome of the patients. Kota Bharu district was identified as the hotspot area of melioidosis in Kelantan. MLST analysis of 33 available clinical and two environmental isolates of B. pseudomallei revealed 15 different sequence types (STs) including seven new emerging novel STs. This study indicates the genetic diversity of B. pseudomallei in Kelantan with the highest ST diversity in Bachok (67%). The most predominant genotype in the research population is ST371 (17.1%; n=6). Even though the reported STs were not related to the districts in Kelantan, all strains were shown to be closely related to the previously reported Southeast Asia strains. The generated risk map with the variety of existing and novel genotypes circulating in the population is important for the future preventive and management plan of melioidosis in Kelantan.